SEVEN CRITERIA OF TEXTUALITY IN PRAGMALINGUISTIC ANALYSIS OF ADVERTISING TEXTS (Scientific journal of the Fergana State University, 2023)
This article discusses seven criteria for the textuality of a text, such as: cohesion, coherence, intentionality, perceptibility, informativeness, situationality and intertextuality. The analysis of these textuality criteria serves to successfully construct an advertising text, which will improve the quality of advertising and increase the sale of goods and services.